2014
DOI: 10.1021/es503723g
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Intrusion Screening Model for the Evaluation of Risk-Based Vertical Exclusion Distances at Petroleum Contaminated Sites

Abstract: The key role of biodegradation in attenuating the migration of petroleum hydrocarbon vapors into the indoor environments has been deeply investigated in the last decades. Very recently, empirical screening levels for the separation distance from the source, above which the potential for vapor intrusion can be considered negligible, were defined. In this paper, an analytical solution that allows one to predict risk-based vertical screening distances for hydrocarbons compounds is presented. The proposed solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 78%
“…The first-order steady-state reactive transport of petroleum vapor hydrocarbons can be described by a one-dimensional (1-D) diffusion differential equation with reaction terms (DeVaull, 2007;Verginelli and Baciocchi, 2014):…”
Section: Vapor Transport and Biodegradationmentioning
confidence: 99%
See 3 more Smart Citations